Physical activity surveillance in the European Union: reliability and validity of the European Health Interview Survey-Physical Activity Questionnaire (EHIS-PAQ). Issue 1 (December 2016) - Baumeister, Sebastian; Ricci, Cristian; Kohler, Simone; Fischer, Beate; Töpfer, Christine; Finger, Jonas; Leitzmann, Michael
Abstract Background The current study examined the reliability and validity of the European Health Interview Survey-Physical Activity Questionnaire (EHIS-PAQ), a novel questionnaire for the surveillance of physical activity (PA) during work, transportation, leisure time, sports, health-enhancing and muscle-strengthening activities over a typical week. Methods Reliability was assessed by administering the 8-item questionnaire twice to a population-based sample of 123 participants aged 15-79 years at a 30-day interval. Concurrent (inter-method) validity was examined in 140 participants by comparisons with self-report (International Physical Activity Questionnaire-Long Form (IPAQ-LF), 7-day Physical Activity Record (PAR), and objective criterion measures (GT3X+ accelerometer, physical work capacity at 75 % (PWC75% ) from submaximal cycle ergometer test, hand grip strength). Results The EHIS-PAQ showed acceptable reliability, with a median intraclass correlation coefficient across PA domains of 0.55 (range 0.43–0.73). Compared to the GT3X+ (counts/minutes/day), the EHIS-PAQ underestimated moderate-to-vigorous PA (median difference -11.7, p -value = 0.054). Spearman correlation coefficients (ρ) for validity were moderate-to-strong (ρ's > 0.41) for work-related PA (IPAQ = 0.64, GT3X + =0.43, grip strength = 0.48), transportation-related PA (IPAQ = 0.62, GT3X + =0.43), walking (IPAQ = 0.58), and health-enhancing PA (IPAQ = 0.58, PAR = 0.64, GT3X + =0.44, PWC75%  = 0.48), and fair-to-poor (ρ's < 0.41) for moderate-to-vigorous aerobic recreational and muscle-strengthening PA. Conclusions The EHIS-PAQ showed good evidence for reliability and validity for the measurement of PA levels at work, during transportation and health-enhancing PA.